The Relationship between Stress Levels and The Incidence of Primary Dysmenorrhea in Grade 10 Female Students - Muhammad Bagus Andrianto; Melly Herawati; Bintang Agustina Pratiwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aim was to determine the relationship between stress levels and the incidence of primary dysmenorrhea in tenth-grade female high school students. The research method used an observational analytic approach with a cross-sectional approach. A sample of 129 female students was drawn using a total sampling technique. The results showed that 50 (38.8%) female students had severe stress levels, 30 (23.3%) had mild stress, and 96 (74.4%) had primary dysmenorrhea. Bivariate analysis showed a significant relationship between stress levels and primary dysmenorrhea (p-value = 0.001). In conclusion, the majority of tenth-grade female students at SMA Negeri 4 Bengkulu City in 2013 had severe stress levels (38.8%), and the majority experienced primary dysmenorrhea (74.4%). The results of the bivariate analysis using the Chi-Square test showed a significant relationship between stress levels and the incidence of primary dysmenorrhea, with a p value of 0.001 (p < 0.05). This finding indicates that the higher the stress levels experienced by adolescent girls, the greater the likelihood of primary dysmenorrhea. The results of this study emphasize the importance of promotive and preventive efforts through reproductive health education and stress management in adolescents to reduce the incidence of primary dysmenorrhea. Keywords: Primary Dysmenorrhea, Stress Level